Nitrogen-Doped Porous Carbon Material Derived from Biomass of Beancurd as an Efficient Electrocatalyst for Oxygen Reduction and Zn-air Fuel Cell. Issue 8 (14th May 2020) - Zheng, Hongying; Zhang, Yun; Long, Jilan; Li, Rong; Gou, Xinglong
Abstract : Developing efficient and affordable electrocatalysts for oxygen reduction reaction (ORR) is very important for next-generation energy conversion and storage devices. Herein, N-doped carbon materials with high N-doping level (5.02 at%) and hierarchically porous structure (H-NHPC) were fabricated by pyrolysis of inexpensive beancurd soaked with urea and NaCl, which was employed as an extra nitrogen resource and a green template to control the morphology and porosity, respectively. The as-prepared H-NHPC exhibited better ORR catalytic activity than the benchmark Pt/C electrocatalysts and most of other biomass-driven nitrogen-doped carbon materials in alkaline medium. The excellent catalytic activity of H-NHPC was attributed to its high content of catalytic active species such as pyridinic-N and graphitic-N, large surface area (988.2 m 2 g −1 ) and abundant porosity ranging from micro- to meso- and macro-scale for efficient mass transfer. Furthermore, the Zn-air battery (ZAB) assembled with H-NHPC as the air electrode displayed higher power-density, larger specific-capacity and better rate-capability than the Pt/C-based ZAB, showing great application perspective in metal-air batteries.